2019
DOI: 10.1016/j.jid.2018.06.190
|View full text |Cite
|
Sign up to set email alerts
|

An Ex Vivo Human Tumor Assay Shows Distinct Patterns of EGFR Trafficking in Squamous Cell Carcinoma Correlating to Therapeutic Outcomes

Abstract: EGFR overexpression is associated with squamous cell carcinoma development. Altered endocytosis and polarization of receptor tyrosine kinases, including EGFR, affect migration and invasion in three-dimensional culture. These studies have been completed via genetic sequencing, cell line, or three-dimensional in vitro and in vivo murine models. Here, we describe an imaging method that allows ex vivo examination of ligand-induced endocytosis of EGFR in non-dissociated human tumors. We analyzed sets of tumor sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
(50 reference statements)
4
18
0
Order By: Relevance
“…This also eliminates the need for early animal sacrifice to assess outcomes, although the advantage of histopathological analysis remains accessible at the end of the experiment. although recent data has illustrated that receptor trafficking and polarisation can influence the metastatic potential (189,224). In combination with previous findings from our laboratory, our data supports EGFR as a driver of PNS in cSCCHN rather than the process of perineural invasion and spread engendering EGFR overexpression (66).…”
Section: Optimisation Of An In Vivo Model To Study Pnssupporting
confidence: 89%
See 2 more Smart Citations
“…This also eliminates the need for early animal sacrifice to assess outcomes, although the advantage of histopathological analysis remains accessible at the end of the experiment. although recent data has illustrated that receptor trafficking and polarisation can influence the metastatic potential (189,224). In combination with previous findings from our laboratory, our data supports EGFR as a driver of PNS in cSCCHN rather than the process of perineural invasion and spread engendering EGFR overexpression (66).…”
Section: Optimisation Of An In Vivo Model To Study Pnssupporting
confidence: 89%
“…Currently, EGFR is not regarded as a prognostic indicator or biomarker in cSCC, and cSCCHN with or without PNI. Whilst associated with metastatic disease, in fully formed tumours there is no clinical correlation of EGFR with tumour growth or patient outcome, although recent data has illustrated that receptor trafficking and polarisation can influence the metastatic potential (189,224). However, in combination with previous findings from our laboratory, our data supports EGFR as a driver of PNS in cSCCHN rather than the process of perineural invasion and spread engendering EGFR overexpression (66).…”
Section: Cscchn Overexpress Egfr Highlighting Its Potential Role In Psupporting
confidence: 46%
See 1 more Smart Citation
“…EGFR is a member of the ErbB receptor family. Studies have shown that EGFR overexpression may be associated with tumor cell proliferation, invasion, metastasis, apoptosis, and angiogenesis in a variety of solid tumors and that EGFR mutations contribute to the malignant transformation of epithelial cells [30]. In this study, EGFR protein expression was significantly inhibited as Bim protein expression increased, which may be the mechanism by which MT1JP inhibits the invasion and migration of A549 cells.…”
Section: Discussionmentioning
confidence: 53%
“…Based on these assumptions, endocytosis inhibitors can be used to move tumor cell antigens targeted by therapeutic monoclonal antibodies to the cell surface, in order to improve the ADCC and clinical responses to these agents. An ex vivo human tumor assay has shown distinct patterns of EGFR trafficking in SCC, correlating with therapeutic outcomes [ 21 ]. The study shows that tumors can be classified into those where EGF was, or was not, able to be endocytosed.…”
Section: Anti-pd-1 and Anti-pd-l1 Antibodies And Endocytosismentioning
confidence: 99%